2023
DOI: 10.1039/d3cc02792a
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric alkene–alkene reductive cross-coupling reactionviavisible-light photoredox/cobalt dual catalysis

Abstract: The first example of asymmetric alkene-alkene reductive coupling is demonstrated via visible-light-fueled photoredox/cobalt dual catalysis. The desymmetrization reaction provided products (>20 examples) with up to five chiral centers in single-step...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…[52] With the concomitant rise in the above technology, great emphasis has been given to asymmetric carbon-carbon and carbon-heteroatom bond formation under photocatalytic conditions. [49,[53][54][55][56] In this context, the key step for the synthesis of chiral heterocycles is asymmetric carbon-heteroatom bond formation, which can be achieved under photocatalytic conditions. In 2016, an exciting review demonstrated a detailed view of visible-light-induced heterocycle synthesis and functionalization in the form of achiral version.…”
Section: Introductionmentioning
confidence: 99%
“…[52] With the concomitant rise in the above technology, great emphasis has been given to asymmetric carbon-carbon and carbon-heteroatom bond formation under photocatalytic conditions. [49,[53][54][55][56] In this context, the key step for the synthesis of chiral heterocycles is asymmetric carbon-heteroatom bond formation, which can be achieved under photocatalytic conditions. In 2016, an exciting review demonstrated a detailed view of visible-light-induced heterocycle synthesis and functionalization in the form of achiral version.…”
Section: Introductionmentioning
confidence: 99%